2008
DOI: 10.1186/1742-4690-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in HIV-1 R5 macrophage-tropism correlates with sensitivity to reagents that block envelope: CD4 interactions but not with sensitivity to other entry inhibitors

Abstract: Background: HIV-1 R5 viruses cause most of the AIDS cases worldwide and are preferentially transmitted compared to CXCR4-using viruses. Furthermore, R5 viruses vary extensively in capacity to infect macrophages and highly macrophage-tropic variants are frequently identified in the brains of patients with dementia. Here, we investigated the sensitivity of R5 envelopes to a range of inhibitors and antibodies that block HIV entry. We studied a large panel of R5 envelopes, derived by PCR amplification without cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(131 citation statements)
references
References 72 publications
11
115
5
Order By: Relevance
“…Moreover, compared to Envs from the other regions, those from the cerebellum infected primary macrophages and the CD4 low RC49 cells less Fig. 1 and described in Tables 1 and 2. efficiently, consistent with reports that efficient infection of macrophages in vitro correlates with the capacity to use low CD4 levels and with increased sensitivity to sCD4 (29,32,(77)(78)(79). Variability in sCD4 neutralization and infection of macrophages suggests that the viruses in different brain regions of ET94 evolve with different CD4 requirements that may expand tropism.…”
Section: Characteristics Of R5 Shiv-infected Macaques With Encephalitissupporting
confidence: 73%
“…Moreover, compared to Envs from the other regions, those from the cerebellum infected primary macrophages and the CD4 low RC49 cells less Fig. 1 and described in Tables 1 and 2. efficiently, consistent with reports that efficient infection of macrophages in vitro correlates with the capacity to use low CD4 levels and with increased sensitivity to sCD4 (29,32,(77)(78)(79). Variability in sCD4 neutralization and infection of macrophages suggests that the viruses in different brain regions of ET94 evolve with different CD4 requirements that may expand tropism.…”
Section: Characteristics Of R5 Shiv-infected Macaques With Encephalitissupporting
confidence: 73%
“…Therefore, our observations support previous conclusions that replication capacity in macrophages does not correlate with an ability to use CCR5 (59). Because we did not observe significant differences in CD4 receptor use, however, we cannot directly corroborate that CD4 affinity predominately influences macrophage tropism as has been previously suggested (59).…”
Section: Discussioncontrasting
confidence: 38%
“…6). Previous studies and our controls suggest that these measurements could be surrogate markers for coreceptor affinity and fusion kinetics (59,66). Because cell entry is potentially the rate-limiting step in HIV-1 replication (3,44,65), in the aggregate, our data suggest that increases in replication capacity over the course of infection are potentially related to greater affinity for the CCR5 receptor and/or faster fusion kinetics.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous studies demonstrated that alterations in gp120-CD4 interactions can impact viral infectivity and membrane fusion (8,22,31,32). To investigate whether reductions in ibalizumab susceptibility affect these Env-mediated functions, we assessed the in vitro infectivities of paired day 0 and week 9 virus isolates by comparing reporter gene expression levels in the HIV-1 entry assay.…”
Section: Vol 85 2011 Ibalizumab Susceptibility Of Hiv-1 3873mentioning
confidence: 99%